2021
DOI: 10.1155/2021/6363571
|View full text |Cite
|
Sign up to set email alerts
|

Hotel Construction Management considering Sustainability Architecture and Environmental Issues

Abstract: Sustainable development and environment in the activities of the construction industry has attracted the attention of experts in most countries of the world. One of the obvious and problematic features of the construction industry of countries is the use of modern building materials using traditional construction methods. Changing the paradigm for sustainable buildings requires a change in the architectural design process. Today, smart buildings are buildings that are at a lower level in terms of energy consum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 125 publications
0
8
0
1
Order By: Relevance
“…Accordingly, it can be argued that the development of criteria and their prioritization for each organization or industry is of great importance and that managers and custodians should make great efforts to implement codified strategies. In addition, due to continuous environmental changes, selecting the most important strategies and implementing them are of great importance in today's world [55][56][57][58].…”
Section: Fuzzy Dematel Methodmentioning
confidence: 99%
“…Accordingly, it can be argued that the development of criteria and their prioritization for each organization or industry is of great importance and that managers and custodians should make great efforts to implement codified strategies. In addition, due to continuous environmental changes, selecting the most important strategies and implementing them are of great importance in today's world [55][56][57][58].…”
Section: Fuzzy Dematel Methodmentioning
confidence: 99%
“…Green roofs reduce energy consumption for heating and cooling. Of the total solar radiation received by the green roof, 27% is reflected, the plant absorbs 60%, and 13% penetrates the soil [78][79][80][101][102][103][104][105]. Studies have shown that green roofing can reduce the heat flow on the roof by 70% to 90% in summer and 10% to 30% in winter.…”
Section: Impact Of Green Roofs On Climate Resilience Enhancement In B...mentioning
confidence: 99%
“…Bununla birlikte yeşil çatılar, sürdürülebilir yapı malzemelerinin kullanımının, kaynak tasarrufu açısından oldukça önemli olduğu otel işletmeciliğinde, doğal havalandırma ve aydınlatma olanaklarından yararlanmak hem maliyet azaltma hem de doğal dengenin korunmasına yönelik etkin sonuçlar ortaya çıkaracaktır (Demir, 2020: 163). Akıllı ve sürdürülebilir binaların tasarımında çevre dostu malzemelerin kullanılması, binanın ömrünü uzatmakta ve sürdürülebilir mimari tasarımına yönelik etkin bir adım atılmaktadır (Kadaei et al, 2021).…”
Section: Tasarım Ve İnşaat Aşamasıunclassified